Effects of puerarin on the intervertebral disc degeneration and biological characteristics of nucleus pulposus cells. (31st December 2023) - Tang, Hengtao; Zhang, Song; Lu, Xinchang; Geng, Tongyu
Abstract: Context: Intervertebral disc degeneration (IDD) is the pathological basis of spinal degenerative diseases. Puerarin (PU) is an isoflavonoid with functions and medicinal properties. Objective: To explore the effect of PU on IDD and its potential mechanism of action. Materials and methods: Sprague-Dawley (SD) rats were divided into sham, IDD, low PU, and high PU groups. Rat nucleus pulposus cells (NPCs) were isolated and divided into control, IL-1β, 100 and 200 μmol/mL PU, TAK-242 (TLR4 inhibitor), or 200 μmol/mL PU + LPS (TLR4 activator) groups. The water content, inflammatory factors, proliferation activity, TLR4/NF-κB pathway activity, apoptosis rate, protein expression of apoptosis, and histology of the extracellular matrix (ECM) were analysed. Results: In vivo : Compared with the IDD group, disorganization of intervertebral disc tissue was significantly improved, water content (2.80 ± 0.24 mg, 3.91 ± 0.31 mg vs. 2.02 ± 0.21 mg) and expression levels of collagen II and aggrecan were significantly increased, and the levels of inflammatory factors and the expression levels of TLR4, MyD88, and p-p65 were significantly decreased in IDD rats treated with PU. In vitro : Compared with the IL-1β group, the proliferation activity of IL-1β-treated NPCs and the expression of collagen II and aggrecan were significantly increased, while the apoptosis rate, levels of inflammatory factors, and the expression levels of TLR4, MyD88, and p-p65 were significantly decreased in IL-1β-treated NPCs treated with PU. LPS reversed the biological function changes of IL-1β-treated NPCs induced by PU. Conclusions: PU can delay the progression of IDD by inhibiting activation of the TLR4/NF-κB pathway.